1991
DOI: 10.1021/j100163a029
|View full text |Cite
|
Sign up to set email alerts
|

Simulation studies of the structure and energetics of sorbed molecules in high-silica zeolites. 1. Hydrocarbons

Abstract: Theoretical methods are used to study the adsorption of linear hydrocarbons, C1-C8, in silicalite, H-ZSM-5, and siliceous faujasite. The aim is to model the behavior of sorbed species in zeolites and evaluate the influence of the zeolite structure and composition on the sorption process. The method of calculation is energy minimization using the Born model of solids with specified interatomic potentials. Atom-atom potentials are used to model the zeolite and zeolite-hydrocarbon interactions. The effect of rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
85
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(93 citation statements)
references
References 0 publications
8
85
0
Order By: Relevance
“…TAP reactor data at low coverages show that over , sites are relatively populated with active sites distributed within the zeolite. On increasing the Si/Al ratio, merging of the sites occurs, leading to isolated sites preferentially located on the straight channels of the ZSM-5 catalyst [61].…”
Section: Nature Of Binding Sitesmentioning
confidence: 99%
“…TAP reactor data at low coverages show that over , sites are relatively populated with active sites distributed within the zeolite. On increasing the Si/Al ratio, merging of the sites occurs, leading to isolated sites preferentially located on the straight channels of the ZSM-5 catalyst [61].…”
Section: Nature Of Binding Sitesmentioning
confidence: 99%
“…In order to simplify the analysis, only zeolites that possess straight channels are considered in this work. Although previous studies have demonstrated that the shape traced by the channel path (e.g., straight, sinusoidal) influences alkane adsorption behavior, [19][20][21][42][43][44] zeolites with channels that do not trace straight paths have been omitted because of their small number in the database. However, even among zeolites having only straight channels, the atoms that comprise the channel openings may connect to form circles, ovals, or other shapes, and these shapes are expected to influence the adsorption thermodynamics.…”
Section: Effects Of Channel Diameter and Cross-section For Zeolites Wmentioning
confidence: 99%
“…Several studies have been focused on measuring [16][17][18] or computing [19][20][21][22] thermodynamic adsorption properties and Henry constants for alkane adsorption and then interpreting the results based on a qualitative assessment of the level of confinement. Lower (i.e., more negative) values for the enthalpies and entropies of adsorption are generally associated with more confining features such as small pores, while higher values are associated with less confining features such as large cages.…”
Section: Introductionmentioning
confidence: 99%
“…With other alkane combinations, azeotropic behavior of the adsorbate phase was also encountered. Systematic exploration of binary mixtures in the carbon range C 5 -C 22 led to the identification of the underlying mechanisms.…”
mentioning
confidence: 99%